Design optimization of lay-up and composite material system to achieve minimum buoyancy factor for composite elliptical submersible pressure hull. (March 2015) - Fathallah, Elsayed; Qi, Hui; Tong, Lili; Helal, Mahmoud
Abstract: The design of laminated composite structures is very susceptible to changes in angle of fiber orientation and ply thickness. In the present work, different lay-up sequences for laminates including, cross-ply [0 m /90 n ] s, [90 m /0 n ] s and angle-ply [0 m /± αn ] s, [90 m /± αn ] s, [± α ] ns, are analyzed. The lay-up sequence, orientation and ply number are optimized using three composite materials T700/epoxy composites, T300/Graphite/Epoxy and B(4)/5505 Boron/Epoxy. Minimize the buoyancy factor of the submersible pressure hull is considered as the objective function. The constraints based on the failure strength and the buckling strength of the pressure hull, incorporating both the Tsai–Wu and the maximum stress failure criteria. The finite element analysis and the optimization process are performed using ANSYS. Additionally, a sensitivity analysis is performed to study the influence of the design variables on the optimal structural strength design.